(untitled) (Eduscotech, 2023)
This study aims to analyze the effect of Problem-Based Learning (PBL) on the critical thinking skills of fifth-grade students at SD Negeri Magetan 1. The research used a quasi-experimental design with a pre-test and post-test approach, involving two groups of students: the experimental group taught using PBL and the control group taught using conventional learning methods. The instruments used for data collection included critical thinking ability tests, classroom observation, and student questionnaires. The results showed a significant improvement in the critical thinking skills of the students in the PBL group compared to the control group. Therefore, it can be concluded that PBL has a positive impact on enhancing the critical thinking abilities of fifth-grade students at SD Negeri Magetan 1. This research contributes to the development of effective learning methods that can facilitate the improvement of students’ critical thinking skills in primary education.